The Power-Knowledge Relationship in Media Political Discourse: A Foucauldian Analysis - Evisa Nindya Rimadhani; Dwi Kartikawati (Pusat Publikasi Nusantara, 2026)
This study examines the power–knowledge relationship in media political discourse through a Foucauldian perspective, focusing on how contemporary digital media construct political truth in the era of platform-based communication. The background of this research lies in the transformation of media from a conventional information channel into a digital ecosystem where algorithms, data-driven systems, and platform infrastructures actively shape political narratives and public perception. The objective of this study is to analyze how media function as a discursive apparatus that produces, regulates, and legitimizes political knowledge in society. The research employs a qualitative approach using a narrative literature review design. Data were collected from relevant scholarly books, peer-reviewed journal articles, and academic publications related to Michel Foucault's concepts of power/knowledge, discourse, governmentality, and subjectivity. The data were analyzed through literature reduction, thematic categorization, and critical interpretation to construct a conceptual synthesis. The findings indicate that media play a central role in constructing regimes of truth through mechanisms of selection, framing, repetition, and exclusion of political narratives. In the digital era, these mechanisms are further intensified by algorithmic systems that govern information visibility and user engagement. The discussion also highlights that digital media not only distribute information but also shape political identity and subjectivity through continuous discursive interaction. In conclusion, media political discourse operates as a dynamic power structure where knowledge is continuously produced and contested. This study emphasizes that understanding media requires a critical awareness of their role in shaping truth, power relations, and political subject formation in the digital age.